Evaluasi Manajemen Persediaan Bahan Baku Pupuk Phonska PT. Petrokimia Gresik - , Dewa Nyoman Aritriasmita, Dr. Wakhid Slamet Ciptono, MBA., MPM., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Inventories have an important role in the operations of a company. Inventory requires a systematic management to ensure operations continuity in the company. Companies often have inventory problems, including too much inventory or shortages. Both conditions result in a huge cost. It is therefore necessary to analyze inventory management for optimum inventory levels. In the research conducted in PT. Petrokimia Gresik, the main focus is on fertilizer products produced by the IIB factory PT. Petrokimia Gresik. Material requirements planning begin by forecasting the total demand for raw materials ZA, Kcl and Phosphate Rock for the future (August 2012 to January 2013). Forecasting uses Simple Moving Average. Another aspect is the use of sensitivity analysis and P method. Total forecasting calculations for requirements of raw materials ZA, Kcl, and Phosphate Rock for the 6 coming months was 17,472.44 tons, 45,348.38 tons, and 8,119.41 tons. For sensitivity analysis results, optimum results were obtained for ZA at 930,000 tons, Kcl of 890,000 tons, and Phosphate Rock of 1,190,000 tons. As well as the calculation by using P method, results of safety stock were obtained for ZA at 12,717.29 tons, while Kcl at 6,186.486 tons, and Phosphate Rock at 7,043.259 tons.